2008
DOI: 10.1086/590510
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Interference Between Animal Species

Abstract: Although sexual interactions between species (reproductive interference) have been reported from a wide range of animal taxa, their potential for determining species coexistence is often disregarded. Here, we review evidence from laboratory and field studies illustrating that heterospecific sexual interactions are frequently associated with fitness loss and can have severe ecological and evolutionary consequences. We define reproductive interference as any kind of interspecific interaction during the process o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
665
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 515 publications
(682 citation statements)
references
References 206 publications
(394 reference statements)
9
665
1
7
Order By: Relevance
“…For example, heterospecific male–male competition can result in reproductive interference (Groning & Hochkirch, 2008). To date, heterospecific competition has been considered mostly in terms of direct contests over territories or other shared resources (Peiman & Robinson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, heterospecific male–male competition can result in reproductive interference (Groning & Hochkirch, 2008). To date, heterospecific competition has been considered mostly in terms of direct contests over territories or other shared resources (Peiman & Robinson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…2002; Arif et al. 2007; Gröning and Hochkirch 2008). In such cases, there is often a mismatch between a species' realized distribution – where it actually occurs – and its potential distribution, which includes all habitat areas that are climatically suitable.…”
Section: Introductionmentioning
confidence: 99%
“…Reproductive interference is defined as an inter‐specific interaction associated with courtship or mating that negatively affects the fitness of at least one of the associated species (Gröning & Hochkirch, 2008). For example, males attempt to mate with both conspecific females and heterospecific females in many animal species.…”
Section: Introductionmentioning
confidence: 99%
“…Even when no hybrid offspring are produced, harassment by heterospecific males may reduce female fitness via energy wasted in repeated rejections of persistent males and costs or injury associated with mating (especially if forced). Some authors have suggested that patterns of species coexistence might be shaped by reproductive interference rather than the more commonly studied process of resource competition (see review in Gröning & Hochkirch, 2008). …”
Section: Introductionmentioning
confidence: 99%